Identification of Leading Sector and Cluster Analysis of Regencies in Kalimantan - Eki Darma Putra; Maria Christina Yuli Pratiwi (Economics Development Analysis Journal, 2019)
To achieve the purpose of regional economic development, there is a need for development policy that is based on the characteristics of the region. Kalimantan is the centre of development in Eastern Indonesia which has strategic position for cooperation region. This study aimed to identify the potential leading sectors to develop and determine the regencies grouping and the characteristics of each group based on welfare indicators. The secondary data were collected from socio-economic data of 56 regencies during 2010-2016. This study used descriptive quantitative method and several analysis theories namely Klassen’s Typology, factor and cluster, Location Quotient, Shift Share, and Overlay analysis. The results of study showed that: (1) the economic structure of Kalimantan had shifted because a change of economic contribution from agriculture to industrial sector; (2) the mining and quarrying, water supply, waste management and recycling sector were the leading sectors in Kalimantan; (3) Kalimantan was classified into four clusters based on 13 economic social indicators: agricultural, urban, disadvantaged, and wealth cluster; (4) the priority of development in each cluster were economic, social, and educational issues.